Identity politics in central Asia and the muslim world. Nationalism, ethnicity and labour in the twentieth century - SCHENDEL, WILLEM Van (I B Tauris Pub., 2001)
Identity politics in central in central Asia and the muslim world. Nationalism, ethnicity and..